TINDAK TUTUR DALAM INTERAKSI DI KALANGAN REMAJA DI LINGKUNGAN NUSANTARA KECAMATAN MANDAU: KAJIAN SOSIOPRAGMATIK - Seppi Yeni; Diana Sari; Hermandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the main issue raised, which is how teenagers in Nusantara Rt 3, District Mandau adhere to the principles of linguistic politeness and whether there are violations of these principles during their communication and interactions. The objective of this research is to describe the adherence to and violations of the principles of linguistic politeness among teenagers in Nusantara Rt 3, District Mandau. This research employs a qualitative descriptive approach. The subjects of the study are conversations or interactions among teenagers in Nusantara Rt 3, District Mandau, while the informants consist of several teenagers residing in the area. Data collection techniques include observation, documentation, and interviews. Data validity is enhanced through source and method triangulation, while data analysis employs qualitative descriptive analysis techniques (identification, classification, description, and analysis). The results indicate that adherence to the principles of linguistic politeness among teenagers in Nusantara Rt 3, District Mandau during interactions or speech acts reveals four maxims that are followed: the maxim of wisdom, the maxim of generosity, the maxim of appreciation/praise, and the maxim of simplicity/humility. Violations of the principles of linguistic politeness in Nusantara Rt 3, District Mandau were found in four maxims that were breached: the maxim of wisdom, the maxim of generosity, the maxim of appreciation/praise, and the maxim of simplicity/humility.